IDENTIFIKASI BAKTERI DAN JAMUR PADA AIR CONDITIONER (AC) DI RUANG PERKULIAHAN FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - UTARI SEPTIA DHARMA; ANCE ROSLINA (LP2MTBM MAKARIOZ, 2020)
Air Conditioner (AC) is one of the most common used facilities for air conditioning. Air conditioners that are rarely cleanedand poorly maintained are a convenient place for the breeding of microorganisms (bacteria and fungi), which hasimplications for the decline in human health and activity. The existence of microorganisms can be influenced by variousfactors, namely temperature, humidity, lighting, occupancy density, ventilation system, the nature and activities of individualsin the room. The purpose of this research was to identify the bacteria and fungal on Air Conditioners in the Faculty ofMedicine, University of Muhammadiyah North Sumatera class. This research was a descriptive observational study using 14samples of dust smears taken from the AC filter. Data analyzed used distribution table. Most of the grown bacteria was GramPositive Bacillus Subtilis are 10 samples (66.7%) and half of the identified mold growth was Penicillium sp. are 7 samples(50%). The highest number of colony found was 32 x 109 x 102 CFU/m3 and the lowest was 0,02 x 102 CFU/m3. There aremicroorganism growth found in the room AC with the most common bacteria found was Bacillus subtilis and the mostcommon fungal growth was Penicillium sp. Despite the growth, more than half the lecture room AC colony number still in therange for air quality qualification are 8 samples (57,1%).